Balancing photosynthesis, O2 consumption, and H2 recycling for sustained H2 photoproduction in pulse-illuminated algal cultures. Issue 8 (20th March 2023) - Vajravel, Sindhujaa; Allahverdiyeva, Yagut; Kosourov, Sergey
Abstract : Sustained H2 photoproduction by green alga Chlamydomonas reinhardtii is achieved under pulse-illumination superimposed on continuous low background light. Pulse-illuminated algae act as biocatalysts producing H2 via direct water biophotolysis. Abstract : Photosynthetic H2 production in unicellular green alga Chlamydomonas reinhardtii is catalysed by O2 -sensitive [Fe–Fe]-hydrogenase (H2 ase) enzymes located in the chloroplast. The process is difficult to sustain due to (i) the inactivation of H2 ase enzymes by O2 coevolved in photosynthesis and (ii) the competition of H2 ases with the Calvin–Benson–Bassham (CBB) cycle for photosynthetic reductants. Our previous studies revealed that H2 production in nutrient-replete algal cultures could be sustained by applying a train of strong but short (1–5 s) light pulses interrupted by longer (3–9 s) dark periods. This limits O2 accumulation produced by photosystem II, prevents activation of the CBB cycle and redirects photosynthetic electrons to H2 ase. In the present research, we demonstrate that the combination of strong light pulses with continuous low background illumination gives a significant gain in the net H2 photoproduction yield by pulse-illuminated algae but only for the first 24 h. We bring evidence that the attenuation of H2 evolution is primarily caused by the accumulation of H2 in the headspace of vials rather than O2 inhibition of the H2 ase, whereas an increase in the H2 partial pressure leads to activation of H2 recycling and noticeable H2 uptake, which is accelerated by O2 . We predicted that sustained H2 production in pulse-illuminated algae, which are additionally exposed to continuous low background light, could be achieved by decreasing the H2 partial pressure in cultures and preventing excessive accumulation of O2 . Indeed, the application of periodic refreshments of a headspace atmosphere with argon and the introduction of O2 scavenger l -cysteine allowed the H2 photoproduction activity in algal cultures to be sustained for more than 10 days both under photoheterotrophic and photoautotrophic conditions, and yielding at least 6-times more H2 per litre of the culture than the standard pulse-illumination protocol.